PENGARUH FAKTOR-FAKTOR YANG DAPAT MEMOTIVASI MAHASISWA BERKEINGINAN WIRAUSAHA - Willyanto Kartiko Kusumo; Wawan Setiawan (Jurnal Dinamika Sosial Budaya, 2016)
The purpose of this study was to analyze the influence of self efficacy, tolerance of risk, freedom in work, need for achievement, and readiness to desire instrumentation Gunadarma University students to be entrepreneurs. Type of data used is the primary data. The research method used was survey by an inductive analysis approach to look ways  that  generally used  in  examining the  factors  that  influence the  willingness  of students to become entrepreneurs. Methods of collecting data is using a questionnaire with 100 people as respondents. The sampling technique used was simple random technique (Random Sampling Method). Data were processed and analyzed using SPSS application assistance. Analysis tools used in this study is to test the validity, reliability, multiple regression liniear, pearson correlation, and independent sample t test. These results indicate that the variable of self success, Freedom in Works, and the Necessity of achievement which is a dominant variable in influencing the desire of Semarang University Students to become an entrepreneur.